THE EFFECT OF QUR'AN MUROTAL THERAPY ON INCREASING LEARNING CONCENTRATION IN SCHOOL AGE CHILDREN IN SINDANG PANON RESIDENCE HOUSING, TANGERANG REGENCY - Kusuma, Gita Septiyani; Yuliana, Yuliani (Journal of Vocational Nursing, 2022)
Introduction: Concentration is a way of focusing the mind on something by putting aside other things that are not related. Students who concentrate on learning can be seen from some of their behavior during the teaching and learning process. Methods: This study uses a quantitative descriptive method using a quasi-experimental research design. Sampling in this study used a time series design, by comparing the post-test and pre-test scores with the number of respondents 30 school-age children who were in the Sindang Panon residence. Results: The results in the pre-test and post-test control groups obtained an average value of 102.07 with a standard deviation (pre-test) of 10.215 and (post-test) of 9.903. In the experimental group, the pre-test got an average value of 67.47 with a standard deviation of 9.862, the post-test got a value of 97.73 with a standard deviation of 13,541. In this study, a p value of 0.000 was obtained which can be concluded that there is an influence between learning concentration before and after being given murotal Qur'an therapy. Conclusions: In this study, it was explained that the administration of murotal Al-Qur'an therapy had an effect which was found in the experimental group of students who did not have a low level of concentration, as well as in the control group most of the students had a high level of concentration currently. a